The Effectiveness Of Diagrammatic Flowchart To Enhance Student’s Writing Skill On Procedure Text (A Quasi - Experimental Research in Ninth Grade of SMPN 19 Kota Serang) - Selnistia Hidayani; Anggi Maulidya; Rohman (CV. Era Digital Nusantara, 2024)
This research aim to investigate the effect of using Diagrammatic flowchart to enhance students’ writing skill on procedure text. This study has three research question, they are : 1) How are the students writing skill on procedure text before treatment? 2) How the implementation of Diagrammatic flowchart 3) How is the effectiveness of Diagrammatic Flowchart to enhance students’ writing skill on procedure text. The research design of this study consist of pre-test, treatment and post-test where IX A class acts as experimental class and IX C class acts as control class. To fulfill the purpose of this research the researcher took 60 students in ninth grade as respondents. Then they were divided into two groups, experimental and control. In the process of treatment, the experimental group received Diagrammatic flowchart as learning media, while the control group receive the conventional teaching. After doing t-test, the researcher compared tt with t0 on degree of significance 5% that was 1.67 Therefore, the result of t-test showed that t0 < tt or 1.65 < 1.67